UTILIZATION OF DIGITAL COMIC MEDIA IN INCREASING SKILLS WRITE SHORT STORIES FOR ELEMENTARY SCHOOL STUDENTS - Aini, Nur; Nuroh, Ermawati Zulikhatin (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2025)
In the current era of globalization and technological development, the world of education has entered a period known as the 5.0 era, where technology is not only a tool but also an integral part of human life, including the learning process. In the world of education, technology should be utilized to improve the quality of learning. Quality learning will make it easier for students to achieve their learning objectives. The purpose of this study was to determine the extent of the influence of digital comics on the short story writing skills of fifth-grade students at SDN Gedangan. The method used was a quantitative experiment, one group pretest-posttest design, with a sample size of 15 students. Data analysis was performed using a t-test, and the results showed a sig. value (2-tailed) of 0.000 in the one-sample t-test. The sig. value of 0.000 is less than 0.05, meaning that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Therefore, it can be concluded that the use of digital comic media in teaching short story writing skills to fifth-grade students at SDN Gedangan has improved their skills. The results obtained after conducting the study indicate that digital media tailored to students' needs can serve as a new innovation in classroom learning and foster creative ideas among students.